Efectos de la movilización neurodinámica en el tratamiento fisioterapéutico de adultos con lumbociatalgia. - Castillo Yánez, Narcisa Isolina (2022)
The research corresponds to a bibliographic compilation of articles belonging to the scientific databases: PubMed, Scopus, ProQuest, Cochrane Library y Research Gate with the aim of analyzing the effects of neurodynamic mobilization in the adult population with lumbosciatica, the selected studies rigorously met the inclusion and exclusion criteria. The methodology used was documentary, with an inductive method, descriptive level and design, qualitative approach and retrospective character. Lumbosciatica is one of the musculoskeletal pathologies related to pain of neurogenic origin, it can become disabling and causes degrees of disability in patients who suffer from it. Neural mobilization is useful in patients with low back pain and is defined as the clinical application of the mechanics and physiology of the nervous system, for the manual treatment of musculoskeletal disorders, mobilizes neuro- connective tissue for the purposes of evaluation, diagnosis and treatment, in those patients with mechanosensitive nerve disorders. According to the Scopus database in Ecuador there is no significant documented evidence of neural mobilization in patients with lumbosciatica, this causes ignorance and prevents the implementation of the technique by the local physiotherapist. According to the analysis and interpretation of the articles, sliding and tightening techniques restore the balance of the surrounding nerves and tissues, improving intraneural circulation, increasing functional capabilities, joint ranges of motion, restoring balance, postural control and locomotion in patients.